2020
DOI: 10.1111/bjhp.12431
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of psychological interventions for smoking cessation in adults with mental health problems: A systematic review

Abstract: Purpose. People with long-term mental health problems are heavier smokers than the general population, and suffer greater smoking-related morbidity and mortality. Little is known about the effectiveness of psychological smoking cessation interventions for this group. This review evaluates evidence from randomized controlled trials (RCTs) on the effectiveness of psychological interventions, used alone or with pharmacotherapy, in reducing smoking in adults with mental health problems.Methods. We searched relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…When we undertook a meta‐analysis, we found that bespoke person‐based smoking cessation interventions for people with SMI were more effective than usual care across all time‐points. This is in line with previous reviews suggesting that smoking cessation interventions are effective in people with mental health problems (but not exclusively SMI) [ 13 ] and the general population [ 40 ]. The largest of the three trials ( n = 526) in this meta‐analysis was at low risk of bias (there were some concerns for the other two), meaning that we are reasonably confident in our conclusion.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…When we undertook a meta‐analysis, we found that bespoke person‐based smoking cessation interventions for people with SMI were more effective than usual care across all time‐points. This is in line with previous reviews suggesting that smoking cessation interventions are effective in people with mental health problems (but not exclusively SMI) [ 13 ] and the general population [ 40 ]. The largest of the three trials ( n = 526) in this meta‐analysis was at low risk of bias (there were some concerns for the other two), meaning that we are reasonably confident in our conclusion.…”
Section: Discussionsupporting
confidence: 92%
“…In a subsequent meta‐analysis in SMI [ 12 ], results supported the effectiveness of varenicline at 3 and 6 months and bupropion at 3 months, but data from behavioural programmes were not pooled and were narratively reported to show little effect. A systematic review in adults with mental health problems (but not exclusively SMI) supported the effectiveness of CBT, motivational interviewing and behavioural or supportive counselling, in combination with NRT or pharmacotherapy [ 13 ]. However, it is unclear whether the findings are applicable to adults with SMI, who may require more intensive and tailored support, due to the reasons discussed earlier.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…or analyse prostate cancer findings. No studies were excluded for having a high or unclear risk of bias [29]. In total, 18 studies were included in the final analysis.…”
Section: Plos Onementioning
confidence: 99%
“…68 Psychological interventions with demonstrated efficacy in smoking cessation include cognitive behavioral therapy, motivational interviewing, and support groups. 74,75…”
Section: Lifestyle Modificationsmentioning
confidence: 99%